Pengaruh Online Payment Terhadap Minat Untuk Berzakat Online - Ramadhan, Faizal Huda; Triono, Firly Rio (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2022)
The presence of economic digitization has a lot of impact on the economy, one of which is Financial Technology in paying zakat  Not only does the conventional economic search get the impact of such technology, but the Islamic economy gets the impact. An example is the mechanism in Zakat. Zakat can now be done online through privately owned gadgets or other technologies. It certainly facilitates people, both zakat payers, and zakat recipients. However, not a few people have not fully implemented technological advances in their lives for several reasons. Therefore, researchers researched to find out the influence of online payment on the interest in online zakat of some people in Bogor City. The research was conducted with the dissemination of questionnaires containing several questions about the problem. The results of the study were tested with several statistical tests, such as data feasibility tests (validity and reliability tests), classic assumption tests (normality tests, linearity tests, and heteroskedasticity tests), and hypothesis tests to determine the veracity of the formulation of previous hypotheses. It is then analyzed using simple linear regression analysis to get to conclusions. The results showed that partial online payment influences interest to make a difference online. However, only 21,3% of its influence, the rest was influenced by other variables that were not present in this study.